Community-level intimate partner violence and the circumstances of first sex among young women from five African countries - Speizer Ilene S; Gómez Anu (BMC, 2010)
Abstract Background Gender-based violence is an important risk factor for adverse reproductive health (RH). Community-level violence may inhibit young women's ability to engage in safer sexual behaviors due to a lack of control over sexual encounters. Few studies examine violence as a contextual risk factor. Methods Using nationally representative data from five African countries, the association between community-level physical or sexual intimate partner violence (IPV) and the circumstances of first sex (premarital or marital) among young women (ages 20-29) was examined. Results In Mali, and Kenya bivariate analyses showed that young women who had premarital first sex were from communities where a significantly higher percentage of women reported IPV experience compared to young women who had marital first sex. Multivariate analyses confirmed the findings for these two countries; young women from communities with higher IPV were significantly more likely to have had premarital first sex compared to first sex in union. In Liberia, community-level IPV was associated with a lower risk of premarital sex as compared to first sex in union at a marginal significance level. There was no significant relationship between community-level IPV and the circumstances of first sex in the Democratic Republic of Congo or Zimbabwe. Conclusion These findings indicate that context matters for RH. Individualized efforts to improve RH may be limited in their effectiveness if they do not acknowledge the context of young women's lives. Programs should target prevention of violence to improve RH outcomes of youth.